2008
DOI: 10.1021/ef700732p
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Structure Transformation of Carbon Anodes during Gasification

Abstract: The crystalline structure transformation of five carbon anodes during gasification in air and carbon dioxide was studied using quantitative X-ray diffraction (XRD) analysis and high-resolution transmission electron microscopy (HRTEM). XRD analysis and HRTEM observations confirmed that anodes have a highly ordered graphitic structure. The examination of partially gasified samples indicated that crystalline structure transformation occurred in two stages during gasification. The first stage involved the consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
5
17
0
Order By: Relevance
“…They attributed this behavior to a balance between the accessibility of the oxidant to the solid atoms, which increases with the extent of LMO, and their reactivity, which decreases with the LMO extent. However, more recent studies involving coal chars [36] and coke [38] argue that the smallest graphitic crystallites are preferentially consumed, leaving behind the larger crystallites, which can be equated to all but the smallest of Oberlin's regions of LMO. Beyond this earlier work, some studies [33,36,38] support the earlier hypothesis [19,21,23] that disordered carbon is preferentially consumed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They attributed this behavior to a balance between the accessibility of the oxidant to the solid atoms, which increases with the extent of LMO, and their reactivity, which decreases with the LMO extent. However, more recent studies involving coal chars [36] and coke [38] argue that the smallest graphitic crystallites are preferentially consumed, leaving behind the larger crystallites, which can be equated to all but the smallest of Oberlin's regions of LMO. Beyond this earlier work, some studies [33,36,38] support the earlier hypothesis [19,21,23] that disordered carbon is preferentially consumed.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies involving coal chars [36] and coke [38] argue that the smallest graphitic crystallites are preferentially consumed, leaving behind the larger crystallites, which can be equated to all but the smallest of Oberlin's regions of LMO. Beyond this earlier work, some studies [33,36,38] support the earlier hypothesis [19,21,23] that disordered carbon is preferentially consumed. They, on the other hand, offer mixed support for the previously hypothesized notion [18,19,21,23] that removal of the more reactive carbon allows the remainder to go on and anneal -Tran et al [38] ruled this possibility out, claiming that the more ordered carbon already existed in their precursor (coke), whilst Sharma et al [33] argued that the ordered structures did not initially exist in their coal char but formed through an oxidative-assisted annealing process.…”
Section: Introductionmentioning
confidence: 99%
“…Each sample of about 50 g was weighed by an analytical balance (MS204S, Mettler Toledo, Columbus, OH, USA) and put in the 100 cm 3 stainless steel cell of the He-Pycnometer. The helium molecules can penetrate into the submicron pores ranging down to 0.3 nm [42]. Consequently, it is possible to measure the volume of the material excluding the pore volume.…”
Section: Analytical Instrumentsmentioning
confidence: 99%
“…An augmentation of the helium density with an increase of carbon conversion from 0 to 35 wt % and a plateau between 35 and 50 wt % could be observed. Tran et al [42] has shown that the gasification of anode particles with a size ranging between 180 and 212 μm shows an increase of helium density from 0 to 10 wt % and a plateau between 10 and 70 wt %. This discrepancy with the present study could be explained by the difference in the initial particle size (for the small particles where the closed pores were probably opened by size reduction) and raw materials.…”
Section: Density Evolution During Gasificationmentioning
confidence: 99%
“…This reaction is known to follow the Langmuir-Hinshelwood model in which the reaction is inhibited by carbon monoxide [5,6]. The Boudouard reaction can be described by a single-step mechanism, if the retarding effect of CO is neglected [7][8][9][10]. When the reactivity tests are performed at atmospheric pressure, the Boudouard reaction is considered to be of the first order (Eq.…”
Section: Introductionmentioning
confidence: 99%